Chromium picolinate, rather than biotin, alleviates performance and metabolic parameters in heat-stressed quail - Şahin, Nurhan; Şahin, Kazım; Onderci, M; Gursu, MF; Cikim, G; Vijaya, J; Küçük, Ömer (Taylor & Francis Ltd, 2005)
1. The effects of chromium picolinate and biotin supplementation alone and in combination on performance, carcase characteristics, malondialdehyde (MDA), vitamin C, vitamin E, glucose and cholesterol levels were evaluated in Japanese quail exposed to high ambient temperature. 2. Two hundred and forty quails ( 10 d old) were assigned randomly to 4 dietary treatments at room temperature ( 22 degrees C; thermoneutral, TN) or ambient ( 34 degrees C for 8 h/d; heat stress, HS). Both TN and HS were fed either on a basal ( control) diet or the basal diet supplemented with 400 mg of Cr/kg ( Cr group), 0.5 mg of biotin/kg of diet ( biotin group) or both (Cr + Biotin group). 3. Supplementing the diet of heat-stressed quails with chromium picolinate improved live weight gain, feed intake, feed efficiency and carcase traits. Biotin supplementation during TN and HS conditions did not have any beneficial effects on body weight gain, feed intake, feed efficiency or carcase traits. 4. Either in combination or alone, chromium picolinate increased serum concentrations of vitamins C and E, but decreased MDA, glucose and cholesterol concentrations in birds kept at high ambient temperature. There was no difference in vitamins C and E and MDA concentrations between birds given chromium picolinate and birds receiving chromium picolinate plus biotin, while glucose and cholesterol levels were significantly lower in all groups. The lowest concentrations of cholesterol and glucose were found in the combination group under both TN and HS conditions. An interaction between diet and temperature was detected for glucose and cholesterol concentrations. 5. Excretion rates for zinc, iron and chromium were lower in TN groups than in the corresponding HS groups. Supplementing diet with chromium picolinate and chromium picolinate plus biotin decreased excretion of minerals while biotin alone did not effect excretion of minerals. 6. Chromium supplementation, but not biotin supplementation, attenuated the decline in performance and antioxidant status resulting from heat stress.
Keywords: Ascorbic-Acid Supplementation; Laying Hens; Dietary Chromium; Antioxidant Properties; Manganese Proteinate; Ambient-Temperature; Growth-Performance; Lipid-Peroxidation; Serum Metabolites; Egg-Production